Offshoring and unemployment: the role of search frictions and labor mobility - Devashish Mitra; Priya Ranjan (Institute for the Study of Labor (IZA), 2009)
In a two-sector, general-equilibrium model with labor-market search frictions, we find that wage increases and sectoral unemployment decreases upon offshoring in the presence of perfect intersectoral labor mobility. If, as a result, labor moves to the sector with the lower (or equal) vacancy costs, there is an unambiguous decrease in economywide unemployment. With imperfect intersectoral labor mobility, unemployment in the offshoring sector can rise, with an unambiguous unemployment reduction in the non-offshoring sector. Imperfect labor mobility can result in a mixed equilibrium in which only some firms in the industry offshore, with unemployment in this sector rising.
urn:nbn:de:101:1-20090513346
Keywords: F11; F16; J64; 330; Trade; offshoring; search; unemployment; Offshoring; Produktivität; Arbeitsuche; Informationskosten; Arbeitslosigkeit; Arbeitsmobilität; Allgemeines Gleichgewicht; Theorie